2019
DOI: 10.1186/s41702-019-0046-y
|View full text |Cite
|
Sign up to set email alerts
|

Trichogenic effect of topical ketoconazole versus minoxidil 2% in female pattern hair loss: a clinical and trichoscopic evaluation

Abstract: Background Female pattern hair loss (FPHL) is a common non-scaring alopecia. Topical minoxidil is the only approved treatment for FPHL; however, it has frequent side effects. Ketoconazole is an antifungal with anti-androgenic properties. Methods The aim of this work was to evaluate the safety and possible trichogenic effects of ketoconazole in FPHL. Patients were randomly assigned into Group A with 20 patients who received 2% topical minoxidil solution and Group B involving 20 patients who were treated by 2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Whereas a significant difference between baseline and months 4 and 6 was observed among those receiving topical minoxidil, significant improvement with ketoconazole was observed only at month 6, suggesting delayed treatment efficacy with ketoconazole. However, whereas treatment-related side effects were reported among 55% of those receiving minoxidil, side effects were reported in only 10% receiving ketoconazole, and there was no difference in patient satisfaction between the groups [42]. These studies highlight the potential therapeutic role of cortisol inhibition on hair regrowth in patients with both male and female-pattern androgenetic alopecia, although additional large, randomized controlled trials are needed to better assess efficacy.…”
Section: Stressmentioning
confidence: 88%
See 1 more Smart Citation
“…Whereas a significant difference between baseline and months 4 and 6 was observed among those receiving topical minoxidil, significant improvement with ketoconazole was observed only at month 6, suggesting delayed treatment efficacy with ketoconazole. However, whereas treatment-related side effects were reported among 55% of those receiving minoxidil, side effects were reported in only 10% receiving ketoconazole, and there was no difference in patient satisfaction between the groups [42]. These studies highlight the potential therapeutic role of cortisol inhibition on hair regrowth in patients with both male and female-pattern androgenetic alopecia, although additional large, randomized controlled trials are needed to better assess efficacy.…”
Section: Stressmentioning
confidence: 88%
“…Lastly, a 2019 study compared the efficacy of 2% topical ketoconazole in comparison to 2% minoxidil among patients with FPAnA [42]. Whereas a significant difference between baseline and months 4 and 6 was observed among those receiving topical minoxidil, significant improvement with ketoconazole was observed only at month 6, suggesting delayed treatment efficacy with ketoconazole.…”
Section: Stressmentioning
confidence: 99%
“…Kubicki et al reported a case of non-scarring hair loss secondary to androgenic alopecia who developed pink discolouration of the hair with 2% ketoconazole shampoo [ 22 ]. Another study by Ahmed et al found that ketoconazole shampoo was associated with contact dermatitis in 10% of the study participants [ 23 ]. However, luliconazole’s lack of serious adverse effects is encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Two controlled trials have shown that the topical administration of a 0.1% melatonin solution greatly promotes the growth phase of hair (known as anagen) in both male and female individuals with AGA. Furthermore, this treatment has been found to be well-tolerated by the participants [49] .…”
Section: Melatoninmentioning
confidence: 97%